Nexus of embodied land use and greenhouse gas emissions in global agricultural trade: A quasi-input–output analysis. (10th September 2020) - Niu, Beibei; Peng, Sha; Li, Cai; Liang, Qi; Li, Xinju; Wang, Zhen
Abstract: The increasing demand for food from a growing global population will accelerate the trade in agricultural products and related land use and greenhouse gas (GHG) emission displacement. Because agricultural land and GHG emissions are inextricably interrelated, understanding the transfer characteristics and nexus of agricultural land and GHG emissions along supply chains is of great significance for formulating sustainable management strategies for environmental protection in agricultural development. Therefore, this study used a network approach, referred to as the "quasi-input–output" model, to simultaneously track agricultural land and GHG emission flows embodied in global agricultural trade among 151 individual countries/regions in 2016; a nexus strength indicator was then applied to explore the interdependencies of land and emissions in different economic systems. The findings indicate that Australia, the USA, Brazil, and Argentina were the top four largest exporters of both agricultural land and GHG emissions. China and the USA were the top two net importers of land use and GHG emissions. Nexus analyses indicate that each country had its specific land-emission dependent and source countries/regions. Large amounts of land–emission nexus trade flows were one-way transmissions among the trading countries, mainly from land-rich and less-developed regions to land-scarce and more-developed regions. Strong regional characteristics were found in the agricultural land–emission-yield nexuses of different countries. These results suggest that an international trade structure adjustment according to the land–emission nexus characteristics of each country, and targeted agricultural intensification strategies considering land and emission trade-offs, should be the key leverages for sustainable agricultural development and environmental protection. Graphical abstract: Image 1 Highlights: A quasi-input-output model was used to track trade-embodied resources/emissions. Inter-country land–emission nexus was detected using a nexus strength indicator. Sustainable management suggestions were proposed based on land–emission nexus.